Peran Komik Bergambar dalam Membenahi Kesalahan dalam Percakapan Bahasa Arab Sehari Hari - Hidayat, Tatang; Al Fawwaz, Achmad Faiz; Istianah, Istianah (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
Purpose- Arabic is a language that is rich in meaning, learning Arabic is one of the keys to reading the Quran and the Sunnah of the Prophet Muhammad Shallallahu 'Alaihi Wa Sallam. Such is the case at STIBA Ar Raayah, a high school in which there are students who come from all over the island in Indonesia, to study Arabic. The purpose of this study is to analyze the mistakes of STIBA Ar Raayah students in Arabic dialogue. Design/Methodology/Approach- This research uses a qualitative approach and analytical descriptive method. The researcher acts as the main instrument. Data collection techniques with interviews, observation and documentation. Data analysis techniques with data reduction, data coding, data display and conclusion drawing. The researcher explained the grammatical errors by students and then proposed a new program to overcome this problem. Findings- Based on the results of the research, STIBA Ar Raayah is supported by an Arabic environment and good teaching methods so that none of the students speak except in Arabic. However, even though this school has an environment and is supported by good teaching methods, there are still shortcomings that need to be corrected, and the media used in correcting these errors are comics because comics are considered effective in correcting student errors in dialoguing in Arabic. Research Limitation/Implications- Students who make mistakes in dialogue in Arabic are quite large. Therefore, it is necessary to hold a language improvement program that is appropriate and fun for students. The researcher suggests comics to be a program in analyzing grammatical errors in daily dialogues.